The Ones Left Behind: Policy Coherence and Sustainable Development in Ethiopia - Stenis, Julia van (European Journal of Sustainable Development, 2025)
The United Nations’ 2030 Agenda strives to ‘leave no one behind’. The Policy Coherence for Sustainable Development framework employed by the Netherlands, aims to leverage mutually beneficial relationships in its development cooperation efforts and aspirations towards SDG attainment. The assessment of its merits is situated in the context of Ethiopia’s pastoral communities, investigating the interplay of SDG 13 (climate action) and SDG 16 (peace, justice and strong institutions) as well as the role of resilience in addressing consequential hardships. This research integrates critical and inclusive development theory in understanding the dynamism of the development arena between the Netherlands and Ethiopia, their underlying national policy priorities, and the (non-)inclusive efforts towards pastoral engagement. The qualitative research design employs in-depth interviews and informal meetings with experts and policy makers complemented by a two-step policy analysis. The findings indicate a prominent focus on short-term threat assessments, declining medium-term risk management mechanisms, and unfavourable long-term resilience building efforts dictating the lived experiences of Ethiopia’s pastoralists. Furthermore, the inherently politicized nature of the policy process reveals the dominating ideas, interests and institutions of the Netherlands, Ethiopia, and other international actors in shaping the pastoral policy arena and its outcomes. The substantial and procedural incoherence of policy translates into the continuing marginalization and exclusion of pastoral communities from national and global development agendas. Hence, policy recommendations call for participatory horizontal and vertical dialogues on an international scale and the enhancement of consultative practices in working towards policy coherence and striving to achieve the universal pillar of ‘leaving no one behind’. Keywords: Policy Coherence for Sustainable Development; Climate-Conflict Nexus; Pastoralist Communities; Ethiopia; The Netherlands; Resilience Building; Leaving No One Behind